PROGNOSTIC AND THERAPEUTIC ROLE OF NUCLEAR FACTORkappa B (NF-ÎºB) IN BREAST CANCER - Ahmed, Ayesha (Journal of Ayub Medical College Abbottabad, 2010)
Nuclear Factor- kappa B (NF-ÎºB) is an essential transcription factor that not only modulates cellular responses to stress but also plays a pivotal role in inflammation, immunity, cell cycle growth and survival. NF-ÎºB-regulated genes have been documented to be involved in cellular proliferation and invasion along with tumour related angiogenesis and lymphangiogenesis. Dysregulation of NF-ÎºB associated pathways are seen in multiple malignancies. Its constitutive activation in the clinically aggressive and prognostically poor ER-negative, Her2-neu positive and inflammatory breast cancer could formulate the basis for its evolution as a potential prognostic and therapeutic target. Keywords: Nuclear Factor kappa B, NF-ÎºB, Breast Cancer, ER-negative